The Need For Sharia Accounting On Sharia Business Institutions - Badar Ilahi; Fathur Rohman (Muhasabatuna : Jurnal Akuntansi Syariah, 2022)
Islam as a religion has been placed as an option and also its teachings are used as guidelines in the lives of human beings who embrace it. So that its existence has provided direction in the development of human civilization, especially in the fields of science and technology. The rise of thoughts, discussions and studies on Islamic economics, has had a major influence on the growth of sharia-based business systems in general and Islamic financial institutions in particular. The existence of such a system has been widely experimented with in several countries, such as: Iran, Pakistan and Sudan, as well as Malaysia, and recently Indonesia.